Millennium rage : survivalists, white supremacists, and the doomsday prophecy - Lamy, Philip (Plenum Press, 1996)
As the millennium approaches, apocalyptic fervor is sweeping the nation. Militias, white supremacists, survivalists, and cults have seized upon the Book of Revelation to trumpet their own fractured version of the end of the world. Millennium Rage is the only book that connects the strands of these fringe groups to a tradition that has underpinnings in American culture and mainstream religion. It moreover shows that many of these groups have stolen and twisted apocalyptic religious symbols to fit their own end: gearing up for Armageddon in this world, not the next